Resonance on the Web: Web Dynamics and Revisitation Patterns - Adar, Eytan; Teevan, Jaime; Dumais, Susan (Proceedings of CHI 2009, 2009)
The Web is a dynamic, ever-changing collection of information accessed in a dynamic way. This paper explores the relationship between Web page content change (obtained from an hourly crawl of over 40K pages) and people’s revisitation to those pages (collected via a large scale log analysis of 2.3M users). We identify the relationship, or resonance, between revisitation behavior and the amount and type of changes on those pages. By coupling our large scale log analysis with a complementary user study we explore the intent behind the revisitation behavior we observed. Using the notion of resonance to identify the likely content of interest, we describe a number of ways interaction with changing and revisited information can be better supported. We illustrate how understanding the association between change and revisitation might improve browser, crawler, and search engine design, and present a specific example of how knowledge of both can enable relevant content to be highlighted.